Comparative life cycle assessment of enhanced anaerobic digestion of agro-industrial waste for biogas production. (15th April 2022) - Ugwu, Samson Nnaemeka; Harding, Kevin; Enweremadu, Christopher Chintua
Abstract: The enhancement of anaerobic digestion improves biogas production, but it has some environmental implications. The need to achieve a trade-off between the energy gains and environmental sustainability necessitated this research. In this study, a comparative assessment of the potential environmental impacts of biogas production from enhanced anaerobic digestion of agro-industrial wastes with different enhancement options, biogas utilization and digestate management was carried out. The anaerobic digestions (mono- or co-digestion) of okra and pig wastes were enhanced with polypyrrole magnetite nanocomposites (PPy/Fe3 O4 NPs), nano zerovalent iron (nZVI), magnetite nanoparticles (Fe3 O4 NPs) and alkaline pretreatment (NaOH). The impact categories were analyzed according to these adopted assessment processes: substrate production, substrate transportation and processing, feedstock enhancement (pretreatment, co-digestion and additive supplementation), biogas utilization, and digestate management. From the analyzed results of this assessment, it was revealed that among all other scenarios, the combined enhancement (co-digestion + PPy/Fe 3 O 4 NPs) option had the least global warming potential of 0.0053 kg CO2 -eq/MJ . Based on the energy and environmental performances, the use of combined enhancement, followed by PPy/Fe 3 O 4 NPs only is recommended to minimize the adverse impacts of electricity generation from biogas on the environment. It is further recommended that techno-economic and life cycle cost analysis of the preferred scenario be conducted. Graphical abstract: Image 1 Highlights: Enhanced anaerobic digestion minimizes environmental impacts of biogas-to-power usage. Enhancement production process was the major contributor to all impact categories. Combined enhancement option had overall low values on all impact categories. Life cycle analysis of different anaerobic digestion enhancement options.